Cover Image, Volume 99, Issue 1. (3rd December 2018) - Huang, Yaohua; Ye, Xiaofei P; Doona, Christopher J; Feeherry, Florence E; Radosevich, Mark; Wang, Siqun
Abstract : The cover image is based on the Research Article An investigation of inactivation mechanisms of Bacillus amyloliquefaciens spores in non‐thermal plasma of ambient air by Yaohua Huang et al., DOI:10.1002/jsfa.9198 . Abstract : The cover image is based on the Research Article An investigation of inactivation mechanisms of Bacillus amyloliquefaciens spores in non‐thermal plasma of ambient air by Yaohua Huang et al., DOI:10.1002/jsfa.9198 .